Review analysis for traceability system in halal food supply chain in Malaysia / Nur Najah Nazri, Noorul Huda Sahari and Nadiah Ramlan - Nazri, Nur Najah; Sahari, Noorul Huda; Ramlan, Nadiah (Research Management Institute (RMI), 2022)
Halal and the safety of the food supply chain are among the critical issues reported, especially on the aspect of product recall. The industries seem to lack of awareness, knowledge, and cost in implementing the traceability system inside food premises. This study aims to conduct an in-depth analysis of the concept of the halal food supply and halal traceability system and examine the challenges faced by the industry in the halal food supply chain. The study adopted the qualitative method where the data were collected through documentary and library-based reviews of both primary and secondary literature. The gathered data were analysed by using document and content analysis to review documents related to the research's objectives. The finding indicated that halal supply chain management does not only cover the aspect of the halal status of the raw material but also involves tools, machines, and logistics. It shows that a traceability system is adopted to ensure that information related to halal food and products is available and can be traced along the supply chain. It includes the information before the production, such as the sources and origin of the raw materials.